Impact of active geomagnetic conditions on stimulated radiation during ionospheric second electron gyroharmonic heating. Issue 1 (27th January 2014) - Bordikar, M. R.; Scales, W. A.; Mahmoudian, A.; Kim, H.; Bernhardt, P. A.; Redmon, R.; Samimi, A. R.; Brizcinski, S.; McCarrick, M. J.
<x xml:space="preserve">Abstract</x> Recently, narrowband emissions ordered near the H+ (proton) gyrofrequency (fcH) were reported in the stimulated electromagnetic emission (SEE) spectrum during active geomagnetic conditions. This work presents new observations and theoretical analysis of these recently discovered emissions. These emission lines are observed in the stimulated electromagnetic emission (SEE) spectrum when the transmitter is tuned near the second electron gyroharmonic frequency (2fce) during recent ionospheric modification experiments at the High Frequency Active Auroral Research (HAARP) facility near Gakona, Alaska. The spectral lines are typically shifted below and above the pump wave frequency by harmonics of a frequency roughly 10% less than fcH (≈ 800 Hz) with a narrow emission bandwidth less than the O+ gyrofrequency (≈ 50 Hz). However, new observations and analysis of emission lines ordered by a frequency approximately 10% greater than fcH are presented here for the first time as well. The interaction altitude for the heating for all the observations is in the range of 160 km up to 200 km. As described previously, proton precipitation due to active geomagnetic conditions is considered as the reason for the presence of H+ ions known to be a minor background constituent in this altitude region. DMSP satellite observations over HAARP during the heating experiments and ground‐based magnetometer and riometer data validate active geomagnetic conditions. The theory of parametric decay instability in multi‐ion component plasma including H+ ions as a minority species described in previous work is expanded in light of simultaneously observed preexisting SEE features to interpret the newly reported observations. Impact of active geomagnetic conditions on the SEE spectrum as a diagnostic tool for proton precipitation event characterization is discussed.